PENERAPAN AKUNTANSI KEUANGAN DALAM USAHA MIKRO, KECIL, MENENGAH (UMKM) - Herda Natasya Nethania Nava; Ahmad Fashih Assabil; Fitri Apriliani; M. Masrukhan (Cahaya Ilmu Bangsa, 2024)
Implementing proper accounting for micro small and medium enterprises brings enormous benefits in terms of financial management, monitoring stock performance, and better business planing. Accounting profides a frameworkfor recording financial transactions, tracking accurate financial report, and identifying areas where micro small and medium enterprises can optimize their cost and revenues. Most micro small and medium enterprises have not carried out comprehensive accounting record, even though they have record sales, purchase and cash in out. Good financial reporting helps increase investor and kreditor confidence in the business’s abillity to survive, thus opening the door for future development. Effective accounting integration is not only important invesment for the growth and sustainability of micro small and medium enterprises in the current era.